TGF-β1-based CRISPR/Cas9 Gene Therapy Attenuates Radiation-induced Lung Injury - Zhen, Shuai; Qiang, Rong; Lu, Jiaojiao; Tuo, Xiaoqian; Yang, Xiling; Li, Xu (Current Gene Therapy, 2022)
Background: Radiation-induced lung injury (RILI) is lacking effective therapeutic strategies. In this study, we conducted TGF-β1-based CRISPR/Cas9 gene therapy for RILI. Objective: Mouse lungs were irradiated with a single-dose of 20-Gy gamma rays followed by intravenous administration of Ad-CRISPR-TGF-β1 or Ad- CRISPR-Null. Methods: Haematoxylin and eosin staining, as well as Masson staining, were performed to observe lung morphology. Albumin and IgM concentrations in bronchoalveolar lavage fluid were measured by ELISA. Cytokine levels were measured using ELISA and/or real-time PCR with terminal deoxynucleotidyl transferase-mediated nick-end labelling. Results: Ad-CRISPR-TTGF-β1 improved histopathological and biochemical markers of lung injury, reduced secretion and expression of inflammatory cytokines, and inhibited progression of fibrosis. Importantly, the SK1/S1P axis, which is known to play a key role via S1P1 in TGF-β1-dependent S1PR pattern remodelling, is responsible for promoting fibrosis. Conclusion: Our results indicate novel insights for RILI therapy.
Keywords: gene therapy